An Analysis of Culinary Business Development Strategy in an Islamic Economic Perspective - Salsabila, Karina; Ansori, Miswan; Zahrotun, Zahrotun (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
In this era of globalization, the culinary industry has become a sector that is growing rapidly, both at the local and international levels . Indonesia, with its cultural diversity and abundant culinary riches, is a fertile place for the growth of the culinary business. Among the various factors that influence the success of a culinary business, the right development strategy plays a key role in ensuring business continuity. The culinary sector is also an inseparable part of the lives of Muslim communities, who often follow Islamic economic principles in various aspects of their lives, including business. The principles of Islamic economics, which include justice, togetherness and transparency, can be a valuable guide in designing culinary business development strategies that are sustainable and in line with Islamic values. This study will focus on a culinary company called Idola Snack and Catering which is based in Jepara. Jepara, as one of the cities in Indonesia with a unique cultural and culinary richness, provides an interesting context for studying culinary business development strategies. Using an Islamic economic approach, this research will analyze the development strategies implemented by Idola Snack and Catering, as well as their impact on financial performance, business growth and contribution to the local community. By better understanding how the principles of Islamic economics can be applied in the culinary business, it is hoped that this research can provide valuable insight for culinary industry players, entrepreneurs, academics and observers of Islamic economics in an effort to improve the quality and sustainability of culinary businesses in Indonesia, as well as creating a wider positive impact on society.